The Ancient Roof of Glasgow Cathedral: Its Condition and Restoration - Oldrieve, W T (Proceedings of the Society of Antiquaries of Scotland, 1916)
The cathedral is one of only two in Scotland with a surviving ancient timber roof. The work was necessary in order to prevent a total collapse of the building. There is no evidence that stone vaulting was originally contemplated for roofing. The poor condition of many of the surviving timbers meant that they could not safely be retained. Hidden steel was used to reinforce the roof. The weight of the roof was reduced considerably by the substitution of copper sheeting for lead or slate. Ancient oak was also re-used where possible.